English English - Rao, Rahul Ravi (Kajian dan Reviu Jinarakkhita: Jurnal Gerakan Semangat Buddhayana (Jinarakkhita Review & Studies: Journal of Buddhayana Spirit Movement), 2025)
Pilgrimage is the center of Buddhist Doctrine. Walking on an outer pilgrimage also reflects an inner pilgrimage; it brings out a new identity and connects through the Buddhist doctrine. Dr. Ambedkar completed the Spiritual Pilgrimage one week before his death, as said by Buddha in the Mahāparinibbāna Sutta, clearly showing how important pilgrimage is, and it connects with an important chapter in the revival of the Buddhist Culture of India. Here, the missing link of Dr. Ambedkar being unwell, still with the zeal, compassion, mindfulness, and energy, completed the spiritual journey at four major places associated with the Life of Buddha, which has not been known by followers and admirers on a larger scale in the present generation. This incredible and transformative journey is highlighted in this study. The methodology used in this research is based on Pali Literature and Travelogue details, which define the importance of Buddhist pilgrimage. The exclusive result is to walk on the path of the Buddha prescribed through his teachings by taking a lifetime initiative to attend the mindful pilgrimage, which leads to spiritual self-development and self-actualization. Through this Cultural Study, more people who have faith in Dr. Ambedkar's contribution will walk on the path and get connected to the teachings of Buddha. Such a pristine and transforming Pilgrimage by an esteemed personality who has uplifted the masses carries history along with him, which needs to be re-understood with the help of Pāli literature and Buddhist Culture.